Study of geo-hydrological processes and assessment of hazard and risk in the Banganga Watershed, Nepal - Ghimire, Motilal (Himalayan Journal of Sciences, 2008)
Himalayan Journal of Sciences Vol.2(4) Special Issue 2004 pp.143-4